Fade as Cultural Capital: A Case Study of Young Men’s Culture in a Barbershop in Amsterdam - Ramkishun, Rayn (Universitas Negeri Semarang, 2024)
Fade haircuts are one of the most popular looks these days. The haircut entails cutting the sides and the back of the head as short as possible and making it transition or